Effects of a Portuguese social–emotional learning program on the competencies of elementary school students - Coelho, Vera; Peixoto, Carla; Azevedo, Helena; Machado, Francisco; Soares, Mónica; Espain, Andreia (Frontiers in Psychology, 2023)
It is widely recognized that socio-emotional learning (SEL) interventions can contribute to supporting students’ positive development of socio-emotional skills (SES) and positive relationships with peers and teachers. Thus, interest in promoting students’ SES through universal evidence-based programs is spreading around the world, including in Portuguese schools. This quasi-experimental study examines the efficacy of a SEL classroom-based program, infused into the curriculum, on students’ communication, self-regulation, and classroom peer relationships. Participants included 208 third- to fourth-grade students from three Portuguese public elementary schools: 143 in the intervention group (54.5% boys; Mage = 8.72; SD = 0.61); 65 in the comparison group (52.3% boys; Mage = 8.66; SD = 0.59). Measures included: Study on Social and Emotional Skills (OECD, 2019), parent, child, and teacher versions; and Classroom Peer Context Questionnaire (Boor-Klip et al., 2016), completed by students. The study followed a pre- and post-test design, with a 16-week intervention. For the overall participants, results show a positive effect of the program on students’ assertiveness (family report). For classroom peer relationship variables, a positive effect of the intervention was found for peer conflict and peer cooperation. Effects were analyzed separately by school grade. A statistically significant or marginally significant positive effect of the program on third-grade students’ communication (family report); assertiveness (child and family report); and sociability (teacher report) was found. No effects were found on self-regulation or peer classroom relationship variables. For fourth-grade students, a positive effect was found on self-regulation (child report); self-control (child report); emotional control (teacher report); and assertiveness (teacher report). For fourth-grade students, findings show a positive effect of the intervention on conflict, isolation, cooperation and cohesion. These positive effects support the expansion of this type of intervention when aiming at strengthening SEL in Portuguese school settings, underlining the relevance of embedding SEL into the curricula.